Digital-based Creativity Transformation: Implementation of E-Learning Media at Sanggar Belajar Indonesia in Sungai Mulia Kualalumpur Malaysia - Madziatul Churiyah; Andi Basuki; Rifqi Wafy Azzuhri; Ghina Rahima Izza Ramadhani; Sholikhan Sholikhan (CV. Proaksara Global Transeduka, 2024)
Digital transformation is being implemented in Sanggar Belajar Indonesia, Sungai Mulia Kuala Lumpur, Malaysia, through this community service project. This study aims to assess the effectiveness of digital learning materials in improving students' memory retention compared to traditional teaching methods. The study used a qualitative methodology and involves training teachers in the creation of digital learning materials. Compared to traditional approaches, the results revealed a 42% improvement in students' memory of the material, and 78% of the implementation's success was attributed to teacher preparation. Improved teacher competency in creating digital learning resources suitable for primary school pupils' concrete operational level was the outcome of the extensive training program. A methodical approach that blends ongoing training with the creation of technology-based learning materials has demonstrated the efficacy of digital transformation in education.